Strategi Humas Badan Penyelenggara Jaminan Produk Halal dalam Membentuk Brand Awareness - Pretty , Karisma; Utamidewi, Wahyu; Kusumaningrum, Rastri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The transition from MUI (Indonesian Ulama Council) to the Halal Product Guarantee Agency (BPJPH) in halal certification occurred due to amendments to regulations in Indonesia which are regulated in the Halal Product Guarantee (JPH) Law No. 33 of 2014. Therefore, it is very important to develop an effective strategy to increase BPJPH brand awareness, with the intention that BPJPH's existence will receive wide recognition in Indonesian society. This research uses the PR Mix theory proposed by Thomas L. Harris, using a qualitative method with a descriptive approach. The main objective is to find out how the Public Relations strategy used in building Brand Awareness of the Halal Product Guarantee Agency (BPJPH), in East Jakarta. The research findings reveal that BPJPH Public Relations implements a strategy based on Thomas L. Harris' public relations mix theory, which emphasizes the P.E.N.C.I.L.S. components: Publication, Event, News, Community Involvement, Information or Image, Lobbying and Negotiation, and Social Responsibility, all of which contribute significantly to the formation of Brand Awareness